HUBUNGAN PENERIMAAN DIRI TERHADAP TINGKAT KECEMASAN NARAPIDANA DI LEMBAGA PEMASYARAKATAN KELAS IIA SUBANG - Pratama, Moch Rizki; Wibowo, Padmono (Universitas Nusa Cendana, 2024)
This study examines the relationship between male inmates' self-acceptance and anxiety, particularly in cases of violent theft at Class II A Subang Correctional Institution. Data were collected through surveys and statistical analysis. The results showed that most of the prisoners in the sample had low levels of self-acceptance in several dimensions, including self-values and standards, taking responsibility for actions, accepting criticism and suggestions, and not blaming oneself. Data analysis also revealed a correlation between low self-acceptance and anxiety, particularly in cases of violent theft. In addition, prisoners about to be released often experience anxiety related to social stigma that can affect their mental health. With a focus on feelings of low self-esteem and concerns about the future, prisoners often face challenges in reintegrating into society. This research provides an understanding of the characteristics of prisoners, such as age, education, employment, and marital status, which may influence their criminal behavior. Keywords: Anxiety; Self-Acceptance; Correctional Institution